ANALISIS KINERJA KEUANGAN LEMBAGA AMIL ZAKAT NASIONAL YAKESMA DENGAN MODEL INTERNATIONAL STANDARD OF ZAKAT MANAGEMENT (ISZM) DAN ALLOCATION TO COLLECTION RATIO (ACR) PERIODE 2019-2023 - Safira, Elza Dwi; Waluyo, Bambang; Fatah, Dede Abdul (Yayasan Education and Social Center, 2025)
This study aims to analyze the financial performance of the National Amil Zakat Institute (LAZNAS) YAKESMA during the 2019–2023 period using two evaluation models, namely the International Standard of Zakat Management (ISZM) and the Allocation to Collection Ratio (ACR). The three main aspects analyzed include the efficiency, capacity, and financial effectiveness of the institution. This study uses a quantitative descriptive approach with secondary data in the form of financial statements and annual performance reports of LAZNAS YAKESMA. The results show that in terms of efficiency, the program load ratio has experienced a positive upward trend, while the ratio of operational and collection expenses is relatively stable and still within efficient limits. In terms of capacity, the growth of key receipts and program expenses showed excellent performance, although the working capital ratio was still below the ideal standard. Meanwhile, in terms of effectiveness, most ACR ratios showed significant improvements to reach the very effective category in 2022–2023. Thus, LAZNAS YAKESMA is considered to be able to distribute zakat funds optimally to mustahik. This research is expected to be a reference for other zakat institutions in evaluating and improving financial performance professionally and transparently.